Implementation of an Advanced Nursing Directive for Children With Right Lower Quadrant Pain: Identifying Those Requiring Further Investigation and Improving Flow Metrics. Issue 6 (June 2016) - Thompson, Graham C.; Kwong, Simon; Bobrovitz, Niklas; Yang, Stephanie; Pols, Erin Kate; Stang, Antonia S.; Eccles, Robin C.; Kazoleas, Veronica
Abstract : Objectives: Advanced nursing directives (ANDs) empower nursing staff to provide advanced levels of care before physician assessment. The objectives of this study were (1) to determine whether an AND for right lower quadrant (RLQ) pain could identify children who required any further investigation to diagnose appendicitis and (2) to determine whether children meeting AND criteria had better emergency department (ED) flow metrics compared with those who did not meet the criteria. Methods: Health records of children aged 3 to 17 years presenting to the ED with abdominal pain who were managed using the departmental AND for RLQ pain were reviewed. Primary outcomes included (1) the proportion of patients requiring further investigation to diagnose appendicitis and (2) the time interval from triage to blood draw. Secondary outcomes included additional ED flow metrics, perforation rate, and negative appendectomy rate. Results: An AND was completed for 210 children. Those who met the AND criteria were more likely to undergo further investigation to rule out appendicitis than those who did not meet the criteria (92/137 [67.2%] vs 32/73 [43.8%]; odds ratio [OR], 2.62; 95% confidence interval [CI], 1.40–4.90). Time to blood draw was significantly lower for those children meeting the AND criteria (74 vs 162 minutes, P < 0.001) as was time to hospital admission (271 vs 395 minutes, P = 0.008) and appendectomy (498 vs 602 minutes, P = 0.015). The negative appendectomy rate was 8.6% (5/58) for children meeting the AND criteria and 9.1% (2/22) for those not meeting the criteria (OR, 0.94; 95% CI, 0.14–10.67); the perforation rate was 29.3% (17/58) and 4.5% (1/22), respectively (OR, 8.17; 95% CI, 1.17–380.86). Conclusions: Children presenting to the ED with RLQ pain who meet the AND criteria are more likely to require further investigation to rule out appendicitis and have better department flow metrics than those who do not meet the criteria. Our results provide further evidence of the utility of ANDs in the ED. Abstract : Supplemental digital content is available in the text.